Laurin-Sandrow syndrome with additional associated manifestations - Kantaputra P.N. (2014)
A Thai man with Laurin-Sandrow syndrome (LSS, MIM 135750), the ninth reported case, is described. He had aN underdeveloped nasal bone, scar-like seams under the nose, large heads of mandibular condyles, and brachymesophalangy of toes as newly observed findings of the syndrome. He also had mental retardation. The patient had duplication of ulna, with triphalangeal thumbs, and polydactyly of one finger. The triphalangeal thumbs were non-opposable. Carpal bones were malformed. Mirror image polydactyly of the toes was present. There were nine toes on the right and eight on the left. Joint abnormalities were observed at his elbows, wrists, knees, ankles, fingers, and toes. Synostosis of severely malformed tarsal bones was noted. This appears to be the first case of LSS with anomalies not limited to the nose and limbs. The relationship between LSS, tibial hemimella-polysyndactyly-triphalangeal thumbs syndrome, triphalangeal thumb-polysyndactyly syndrome, preaxial polydactyly types 2 and 3, and Haas-type syndactyly is discussed. © 2001 Wiley-Liss, Inc.